Insights into the diversity and conservation of the chB6 alloantigen - Funk, Phillip E. (Frontiers in Immunology, 2025)
The bursa of Fabricius has been a durable model of B lymphocyte development. Yet there are unique aspects of B- lymphocyte development in the bursa that remain to be elucidated, and these may reveal important functional differences in the avian system and distinct evolutionary mechanisms from the canonical murine and human models of B- lymphocyte development. Our laboratory has been interested in the function of the chB6 alloantigen. ChB6 has three defined alleles and is present on B lymphocytes in chicken from their earliest development at ED 12. ChB6 continues to be expressed through B- lymphocyte ontogeny as well as on a subset of macrophages. We have shown that chB6 ligation by antibody leads to rapid apoptosis. Transfection of cDNA- encoding chB6 replicates this in mammalians cells, suggesting a common signaling pathway, but there remain no clear mammalian homologues. Structurally, the extracellular domain of chB6 is similar to mammalian SLAM (signaling lymphocyte activation molecules) proteins and chB6 partitions into lipid rafts in close proximity to the B- cell receptor. The lack of homology within the intracellular domain remains puzzling. Utilizing genomic resources, we have found a number of similar molecules in both birds and reptiles; however, they show greater conservation in the intracellular domain, including an SH3 motif that we have shown to be critical in inducing apoptosis.